STRUCTURAL SHIFTS IN THE ENGLISH-INDONESIAN NOVEL TRANSLATION: A SYSTEMIC FUNCTIONAL LINGUISTICS ANALYSIS - Nurul Ariefyanti, - (2018)
The linguistic features of each language may differ from one to another. Each language that exists in the world has different structure. The difference in the system structure of the word has been an issue that appears in translation process. Therefore, this study aims to analyze types of structural shifts found in the nominal groups and verbal groups of a novel translation and investigate how the structural shifts affect the meaning. This study follows a descriptive qualitative method by Cresswell (2009). The data of the study are taken from the novel entitled The Fault in Our Stars by Green (2012) and the Indonesian version translated by Nimpoeno (2016). The analysis of the study draws on Gerot and Wignell's (1994) theory of nominal group and transitivity and Catford's (1965) translation theory as the basis of the categorization of the structural shifts. The data analysis reveals that there are two types of structural shifts found in the data. Those are single translation shift that includes: 1) structure shift, 2) unit shift, 3) class shift, and 4) intra-system shift and double translation shift that is the combination of the shifts. The most frequent shifts found in the structural shifts of nominal groups are the combination of structure and class shift (38.94%), followed by structure-intra system shift (40.72%), unit-intra system shift (13.27%), unit shift (6.19%), and unit-class shift (0.88%). On the contrary, the most frequent shift found in the verbal groups is intra-system shift (70.59%) which belongs to the single translation shift. The study shows that structural shifts slightly affect meanings of the translation. This study suggests that linguistic analysis can indicate how learning to translate requires linguistic knowledge of a certain language as the expert translators conduct the translation.-----Terdapat perbedaan fitur linguistic antara satu Bahasa dengan Bahasa lainnya karena struktur setiap Bahasa yang ada memiliki perbedaan. Perbedaan struktur dalam suatu sistem Bahasa tertentu merupakan masalah yang dapat ditemukan dalam proses terjemahan. Oleh karena itu,studi yang berjudul "Structural Shifts in the English-Indonesian Novel Translation: A Systemic Functional Linguistics Analysis" bertujuan untuk menganalisa jenis-jenis perubahan struktur pada nominal grup dan verbal grup dalam novel terjemahan dan menyelidiki bagaimana perubahan struktur yang ada mempengaruhi pembuatan makna. Studi ini menggunakan metode descriptive qualitative yang diusulkan oleh Creswell (2009). Data yang digunakan dalam studi ini berupa teks tulis dari novel yang berjudul "The Fault in Our Stars" yang ditulis oleh John Green dan diterjemahkan oleh Nimpoeno. Data tersebut dianalisi menggunakan teori yang diusulkan oleh Gerot dan Wignell (1994) tentang Nominal Group dan Transitivity. Kemudian, klasifikasi perubahan struktur pada nominal grup dan verbal grup dikategorikan berdasarkan teori Translation Shift yang diusulkan oleh Catford (1965). Studi ini menunjukan bahwa terdapat dua jenis perubahan struktur yang terdapat dalam data yaitu single translation shift dan double translation shift. Dalam analisis peruabahan struktur dalam nominal group diketahui bahwa perubahan yang paling sering muncul adalah kombinasi dari structure shift dan class shift (38.94%). Kemudian diikuti oleh structure-intra system shift (40.72%), unit-intra system shift (13.27%), unit shift (6.19%), dan unit-class shift (0.88%). Sebaliknya, dalam analisis verbal grup, perubahan yang paling sering muncul merupakan jenis single translation shift yaitu intra-system shift (70.59%). Kemudian diikuti oleh oleh kombinasi dari unit dan intra-system shift (15.29%), class dan intra-system shift (7.06%), dan level dan intra-system shift (4.71%). Perubahan yang paling sedikit muncul pada verbal grup berasal dari jenis single translation shift yaitu level shift (2.35%). Studi ini juga menunjukan bahwa terdapat perubahan makna pada data. Melalui analisis linguistik, studi ini mengindikasikan bahwa dalam mempelajari terjemahan membutuhkan pengetahuan linguistik suatu Bahasa tertentu.